Biochemical and physiological characterization of oil palm interspecific hybrids (elaeis oleifera x elaeis guineensis) grown in hydroponics (2013)
The interspecific hybrid, Elaeis oleifera x Elaeis guineensis (OxG) is an alternative for improving the competitiveness and sustainability of the Latin American oil palm agro-industry, because of its partial resistance to some lethal diseases and also because of the high quality of its oil. A comparative characterization was conducted of the physiological and biochemical performance of seedlings of six OxG hybrids grown in hydroponics. Gas exchange, vegetative growth, protein, sugar and photosynthetic pigment content, and antioxidant system activity were determined. With the exception of gas exchange, the other variables showed significant differences between materials. The ‘U1273’ and ‘U1737’ materials showed greater vegetative growth with no expression of biochemical traits, while the ‘U1914’and ‘U1990’ materials showed high levels of reducing and total sugars, photosynthetic pigments, and antioxidant system activities, characteristics that could confer them adaptation to stress conditions. With the standardized hydroponics technique, the optimal conditions for the growth of seedlings were ensured, the differences between materials and hybrid crosses were established, so those with promising features from the physiological and biochemical standpoint were identified. Finally, it could be used to study in a simple, fast, clean and inexpensive way, the effect of levels and sources of mineral nutrients on the growth and development of oil palm.